2007
DOI: 10.1097/01.iae.0000251228.33870.64
|View full text |Cite
|
Sign up to set email alerts
|

A New Heavy Silicone Oil (Hws 46-3000) Used as a Prolonged Internal Tamponade Agent in Complicated Vitreoretinal Surgery

Abstract: HWS 46-3000 was well tolerated, effective in the inferior quadrants with a low incidence of membrane development. The main complication was the high rate of tamponade-related cataract formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 37 publications
1
63
0
3
Order By: Relevance
“…54 HWS 46-3000 is the latest, heaviest and most viscous of the three new tamponades; a clinically significant emulsification could not be observed in the first clinical application of HWS 46-3000 when left in situ for 1-3 months and the initial report with low complication and high success rates are encouraging. 22 However, the higher viscosity also increases the difficulties associated with the handling of the substance, for example, its removal. 22 …”
Section: Heavy Silicone Oilsmentioning
confidence: 99%
See 3 more Smart Citations
“…54 HWS 46-3000 is the latest, heaviest and most viscous of the three new tamponades; a clinically significant emulsification could not be observed in the first clinical application of HWS 46-3000 when left in situ for 1-3 months and the initial report with low complication and high success rates are encouraging. 22 However, the higher viscosity also increases the difficulties associated with the handling of the substance, for example, its removal. 22 …”
Section: Heavy Silicone Oilsmentioning
confidence: 99%
“…20,27 Oxane HD is the lightest of the three new tamponadesFthis might be one of the reasons why slightly higher redetachment rates could be noticed with this substance, when comparing the overall outcomes with other tamponades 21 ( Table 1) as well as individual series with different tamponades conducted within the same institution. 18,22,32 Especially in eyes with previous scleral buckling surgery, relatively light tamponades do not seem to enable an efficient tamponade in the area central to the indent. 19,32 Densiron 68 (Fluoron Co, Neu-Ulm, Germany) is a solution of perfluorohexyloctane (F6H8) and 5000 cSt silicone oil.…”
Section: Heavy Silicone Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown good anatomical and visual outcomes with no emulsification upto 3 months with these agents. [28][29][30] HSO works well as a long-term tamponade agent for complex retinal detachments involving inferior proliferative vitreoretinopathy. 31 …”
Section: Heavy Silicone Oilmentioning
confidence: 99%